Influence of ohmic heating on the flow field in thin-layer electrodeposition - Schröter, Matthias; Claret, Josep; Kassner, Klaus; Rehberg, Ingo; Sagués, Francesc (Physical Review E, 2002)
In thin-layer electrodeposition the dissipated electrical energy leads to a substantial heating of the ion solution. We measured the resulting temperature field by means of an infrared camera. The properties of the temperature field correspond closely with the development of the concentration field. In particular, we find that the thermal gradients at the electrodes act similar to a weak additional driving force to the convection rolls driven by concentration gradients.